2015
DOI: 10.5817/proin2015-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the methods and practises of personal digital information archiving among the student population

Abstract: The issue of personal archiving is one often raised in the context of the fast changing digital era. Even among the "informationally literate" personal digital archiving is more often simply a side-effect of generating content in the digital environment than a planned activity. The aim of this paper is to research the extent to which the student population employs the doctrines of digital curation, digital preservation and digital stewardship. This group is interesting for examining in this context because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…In fact, many studies observed that people still extensively use folders for organizing personal digital files, as previously reviewed. In particular, Marčetić (2015) and Krtalić et al (2016), who asked approximately 220 university students about their personal digital information organizing practices, reported that 94.5 percent (Marčetić, 2015) and 97.4 percent (Krtalić et al, 2016) of the participants organized digital files in folders, which shows that it is a dominant organizing practice for digital files. As shown above, most of the personal information organization studies examined certain aspects of the organization process or the end results of organization.…”
mentioning
confidence: 99%
“…In fact, many studies observed that people still extensively use folders for organizing personal digital files, as previously reviewed. In particular, Marčetić (2015) and Krtalić et al (2016), who asked approximately 220 university students about their personal digital information organizing practices, reported that 94.5 percent (Marčetić, 2015) and 97.4 percent (Krtalić et al, 2016) of the participants organized digital files in folders, which shows that it is a dominant organizing practice for digital files. As shown above, most of the personal information organization studies examined certain aspects of the organization process or the end results of organization.…”
mentioning
confidence: 99%
“…Backup frequency was also noted in different studies, such as continuous backup, once in a week, month, or once in 6 months (Becker and Nogues, 2012); random backup (Krtalić et al, 2016; Marčetić, 2015); and making backup with any defined criteria (Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…Many studies reported the backup practices of personal digital information (Divya and Sudhier, 2018; Hicks et al, 2008; Marshall et al, 2006). People made backup of different types of documents such as official documents (Krtalić et al, 2016; Marčetić, 2015), messages (Zhao et al, 2019), emails, photos, and videos (Krtalić et al, 2016; Sinn et al, 2017; Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The examination indicated that 84% of the people had built up the correct propensity for cleaning their tongue and 71% wash their mouth after dinners in their everyday routine (Rajeshkumar et al, 2018b). The use of mouthrinses with 0.1% or 0.2%, chlorhexidine (CHX) in children, for 6 months, achieved significant reductions for plaque and gingival indices, and no differences for caries increment, compared with a placebo (Marčetić, 2015). With the concurrent application of PTC and a 0.4% or 1% CHX toothpaste in dental students over a period of 2-years, no differences were found in plaque and gingival scores, with the placebo group, while a lower caries increment was observed in the 1% CHX group, when compared to all other groups, concomitantly with a higher number of active non-cavitated lesions becoming inactive (Karthiga et al, 2018).…”
Section: Resultsmentioning
confidence: 99%